Mengenali Facial Palcy pada Trauma Wajah dan Tatalaksana Pembedahan - Gunawan, Gunawan; Hanan Farihah, Inas; Raihan Lutfia, Lisa; Mahfuzzahroni, Muhamad; Febriya Moestafa, Rizka (CV RIFAINSTITUT, 2021)
Bell's palsy is the most common neurological disorder affecting the cranial nerves with an onset that is rapid and unilateral, and it is common cause of facial paralysis worldwide. Bell's palsy occurs due to compression or enlargement of the stylomastoid foramen and causes nerve obstruction or damage caused by trauma, infection, inflammation, autoimmune, ischemic. This article aims to review bell's palsy, specifically motor nerve alignment, surgical disorders and management of bell's palsy. Source searches were carried out on online portals for journal publications such as Google Scholar (scholar.google.com) and the National Centre for Biotechnology Information/NCBI (ncbi.nlm.nih.gov), with the keyword “Facial palcy, dan Bell’s palcy”. In the United States, the annual incidence of Bell's palsy is approximately 23 cases per 100,000 people. Permanent facial paralysis and non-transient functional deficits are the main indications for surgical reconstruction of facial nerve function. The indications for surgery depend on the severity of the nerve lesion, blunt trauma that causes nondegenerative neuropraxia does not require surgical reconstruction, whereas disorders leading to degenerative neurotmesis require surgery.